The Effect of Articulate Storyline Software in Developing ‎Cognitive Flexibility and Environmental Self-awareness ‎among 10th Grade Students - Lababneh ‎, Mahmoud; Obeidat, Hani (Jordan Journal of Educational Sciences, 2021)
This study aimed at revealing the effect of Articulate Storyline software on developing geographical cognitive flexibility and environmental self-awareness of 10th grade Jordanian students. Semi-experimental approach was deployed; a 25- item measured was developed to gauge students’ cognitive flexibility and a 25-question test was developed to gauge students’ environmental awareness achievement. A pilot study was conducted on a sample of 55 students 10th graders from different schools within Al Taybah and Al Wasatyah Directorates of Education - Irbid province to assure the reliability and validity of the study instruments. The sample of the study was divided into two groups: the control group (27 students) was traditionally taught environmental problemsand the pilot group (28 students) was taught environmental problems through Articulate Storyline software. The results revealed that there are statistically significant differences at the level (α≤0.05) between the average of students’ performance in the cognitive flexibility test as well as on the environmental awareness test due to the teaching method in favor of the experimental group. In light of the results, the study recommends the need of deploying Articulate Storyline software in teaching geography